2006
DOI: 10.1158/1535-7163.mct-05-0516
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor–specific antibody attenuates tumor growth, metastasis, and angiogenesis in an orthotopic mouse model of pancreatic cancer

Abstract: Connective tissue growth factor (CTGF) plays an important role in fibrosis by modulating cell migration and cell growth but may also modify tumor growth and metastasis. Because CTGF is overexpressed in pancreatic ductal adenocarcinoma, we investigated the in vitro effects of CTGF on the proliferation and invasiveness of PANC-1 pancreatic cancer cells and examined the consequences of its in vivo inhibition on the growth and metastasis of these cells using a fully human CTGF-specific monoclonal antibody (FG-3019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 55 publications
7
112
1
Order By: Relevance
“…Although CTGF antagonism would be hypothesized to disrupt the fibrotic architecture of PDA tumors, we instead found that FG-3019 treatment left the stromal content grossly intact. Also, in contrast to previous xenograft results with FG-3019 that demonstrated antitumor activity (41,42), treatment with FG-3019 alone did not result in significant antitumoral responses in KPC mice. Previous reports have also described CTGF as a critical mediator of vascular remodeling by regulating pericyte function and endothelial basement membrane formation during angiogenesis (43).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although CTGF antagonism would be hypothesized to disrupt the fibrotic architecture of PDA tumors, we instead found that FG-3019 treatment left the stromal content grossly intact. Also, in contrast to previous xenograft results with FG-3019 that demonstrated antitumor activity (41,42), treatment with FG-3019 alone did not result in significant antitumoral responses in KPC mice. Previous reports have also described CTGF as a critical mediator of vascular remodeling by regulating pericyte function and endothelial basement membrane formation during angiogenesis (43).…”
Section: Discussioncontrasting
confidence: 99%
“…Previous reports have also described CTGF as a critical mediator of vascular remodeling by regulating pericyte function and endothelial basement membrane formation during angiogenesis (43). In the tumor microenvironment, CTGF and the CXCR2 chemokine ligand axis have also been implicated as promoters of tumor angiogenesis in a variety of PDA models (42,44). In contrast to the prior finding that inhibition of CXCR2 resulted in reduced CTGF levels and regulated blood vessel density and tumor growth in the related Ptf1a cre/+ ;LSL-Kras G12D/+ ;Tgfbr2 flox/flox mouse model (44), FG-3019 had no effect on mean vessel density over the time course of treatment in KPC mice, and suggests that the relevant therapeutic targets here are neoplastic cell-intrinsic.…”
Section: Discussionmentioning
confidence: 98%
“…Loss of CCN2 expression in embryonic mesenchymal cells results in diminished cell migration and adhesion, and reduction in pro-angiogenic and profibrotic gene expression (Chen et al 2004;Kennedy et al 2007). Previous studies have shown that application of an antibody specific to CCN2 resulted in decreased tumour volume, metastasis and angiogenesis (Aikawa et al 2006). CCN2 expression is controlled primarily at the transcriptional level; therefore elements in its promoter are likely to contribute to its overexpression in pancreatic cancer (Blom et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…12 CTGF may play a role as a secreted tumor suppressor protein 13 or contribute to promote tumor cell growth and invasion. 14 Some studies suggested that CTGF could also be involved in the inflammatory response. CTGF is a chemotactic factor for monocytes 15 and regulates cellular adhesion and migration in mesangial cells.…”
mentioning
confidence: 99%